Analysis of Bank Health Level Using RGEC (Risk Profile, Good Corporate Governance, Earning, Capital) Method (Study On Bank Muamalat Indonesia Before, During and Post The Covid-19 Pandemic) - Rizki Amalia; Ahmad Mushowwir; Rabaniyah Istiqamah (Jurnal Sinar Manajemen, 2024)
Covid-19 spread very widely in countries which resulted in economic paralysis, including in the banking sector in Indonesia. When the Covid-19 pandemic occurred, banks experienced many obstacles, including Bank Muamalat Indonesia, especially in terms of financing, due to the economic paralysis resulting in the ability to fulfill credit obligations is disrupted, especially in the MSME sector. This condition can affect banking health, where Non-Performing Financing (NPF) can increase significantly. This research aims to analyze the health level of Bank Muamalat Indonesia in 2019-2022 (before, during and after the Covid-19 pandemic). This research is a type of qualitative research with a comparative descriptive approach. Data collection in this research uses secondary data, using documentation methods, the main data source is the annual financial report of Bank Muamalat Indonesia for 2019-2022. The data analysis method uses formulas and conditions in accordance with the RGEC method. The research results show that in 2019 (before the pandemic) Bank Muamalat Indonesia received the title "Quite Healthy" with a composite rating of 60.00%. In 2020-2021 (during the pandemic) it received the title "Quite Healthy" with a composite rating of 60.00% in 2020 and 68.57% in 2021, there was an increase in the composite percentage at the end of the pandemic. And in 2022 (post-pandemic) it will receive the title "Quite Healthy" with a composite rating of 68.57%.